Implications of strategic orientation on firms' performance in a lower middle-income country: Does organizational innovation capability matter? - Marian Maclean; Michael Karikari Appiah; Joyce Francisca Addo (Cogent Business & Management, 2023)
Since the birth and subsequent ratification of United Nations' Agenda 2030 for sustainable development, local businesses are working assiduously to re-strategize and adapt to the changing external environment including responsible consumptions and production in order to gain competitive advantage and improve their performance. To facilitate this call, our paper is aimed to analyse the implications of strategic orientation on firm performance, and develop a model to explain the mediating role of organizational innovation capability on the relationship between strategic orientation and firm performance with a focus on a lower middle-income country where such studies are largely inadequate. Our paper is anchored on positivists' ontology and quantitative approach. Cross-sectional survey data have been elicited from formalized small and medium enterprises (SMEs) that are registered with Ghana Enterprise Agency. Our hypotheses have been tested using Partial Least Square and Andrew Hayes Macro Process techniques. Our results have showed that the dimensions of strategic orientation (marketing, entrepreneurship, and technology) exert positive and significant effects on firms' innovation capability and performance. Besides, organizational innovation capability significantly mediates the relationships between marketing and technological orientations and firms' performance. This study is among the very few to provide strategic orientation model to enhance organizational innovation and performance in the context of lower middle-income country. The emergency of contextual variables that impact on organizational innovation and firm performance would go a long way to guide managers, owners and regulators to develop robust strategies that could enhance the realization of sustainable development goals in the long term.
Keywords: 650; Firm's Performance; Organizational Innovational and Lower Middle-Income Country; Strategic Orientation